Use of radiographic densitometry to predict the bone healing index in distraction osteogenesis - Saw, A.; Manimaran, S.; Faizal, S.; Bulgiba, A.M. (2008)
Bone lengthening with distraction osteogenesis involves prolonged application of an external fixator frame. Qualitative and quantitative evaluation of callus has been described using various imaging modalities but there is no simple reliable and readily available method. This study aims to investigate the use of a densitometer to analyze plain radiographic images and correlate them with the rate of new bone formation as represented by the bone healing index. A total of 34 bone lengthening procedures in 29 patients were retrospectively reviewed. We used an X-Rite 301 densitometer to measure densities of new callus on plain radiographs taken at 4 and 8 weeks after surgery. Patients aged below 16y had significantly lower BHIs indicating faster bone healing and shorter duration of treatment. The ratio of radiographic densities between centre and edge of the new bone measured from plain radiographs taken at 8 weeks correlated positively with the eventual BHI of the patient. This method provides a simple and easy way to predict the rate of bone healing at an early stage of treatment and may also allow remedial action to be taken for those with poor progress in bone formation.